PENDIDIKAN ISLAM DALAM PERSPEKTIF WAHYU PERTAMA (SURAH AL-‘ALAQ AYAT 1-5) - Husaini Husaini (UIN Antasari Banjarmasin, 2020)
ABSTRACT: Islamic education begins with the sending of Muhammad as a prophet and apostle. The first revelation event in Hira Cave involved 3 important interrelated elements, namely the Prophet Muhammad, the revelation or message, and the Angel Gabriel AS. These three elements in the world of education can be understood as the relationship between students, materials, and teachers. The purpose of this paper is to examine the educational aspect in the first revelation (Q.S. al-'Alaq: 1-5), the research method is a library research method. The results of the study illustrate that education can be successful if in the process it cannot be separated from the attitude of the soul -especially for a teacher- who is always connected to God.KEYWORDS: Islamic Education; Revelation; Teacher. ABSTRAK: Pendidikan Islam dimulai dengan diutusnya Muhammad sebagai seorang nabi dan rasul. Peristiwa wahyu pertama di Gua Hira melibatkan 3 unsur penting yang saling terkait, yaitu Nabi Muhammad saw, wahyu atau pesan, dan Malaikat Jibril as. Ketiga unsur tersebut dalam dunia pendidikan dapat dipahami sebagai relasi antara murid, materi, dan guru. Tujuan penulisan ini adalah mengkaji aspek pendidikan dalam wahyu pertama (Q.S. al-‘Alaq: 1-5), metode penelitian adalah metode penelitian kepustakaan. Hasil penelitian menggambarkan bahwa pendidikan dapat berhasil jika dalam prosesnya tidak terlepas dari sikap jiwa -terutama bagi seorang guru- yang senantiasa terhubung dengan Tuhan.KATA KUNCI: Pendidikan Islam; Wahyu; Guru.